Investigating the oil bioremediation capacities of thermophilic bacteria - Mol, Michael (My University, 2020)
Crude oil and petroleum derivatives are released, both inadvertently and actively, into vulnerable environments in vast amounts. As such the development and application of effective remediation approaches are major research imperatives. In particular, the development of environmentally friendly remediation approaches, such as bioremediation are focal points. One promising approach is the bioremediation of oil hydrocarbons using thermophilic bacteria. In Chapter 1 we have reviewed pertinent literature characterising crude oil and petroleum derivatives, their major environmental releases, remediation approaches and contextualised the application of thermophiles in bioremediation. In Chapter 2 we conducted plate- and liquid-based screening assays on a substantial collection of thermophilic bacteria, identifying numerous strains capable of degrading used-motor oil. Furthermore, we identified a number of thermophilic taxa which are capable of oil displacement, most likely linked to the production of biosurfactants. In Chapter 3 we further characterised the oil hydrocarbon degradation capacity of three strains belonging to the genus Geobacillus. This involved whole genome sequencing of these strains, as well as qualitative and quantitative characterisation of the hydrocarbon degradation capacities of the strains using 2D GC/MS analysis. One strain in particular, Geobacillus stearothermophilus Tok5A2 showed great promise in terms of its oil degradation activity. This strain possesses several aliphatic hydrocarbon degradation proteins, including three alkane monooxygenases, LadAαB23, LadAβB23 and LadBB23 which may underlie this capacity
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, Johannesburg, 2020
Keywords: Bioremediation; Thermophilic microorganisms